"This Is the End." A Case Study of a Japanese Learner's Experience and Regulation of Anxiety - Naoko Sano Nakao; Hayo Reinders (MDPI AG, 2022)
This study investigates the role of emotions in second language learning, in particular, that of anxiety. Research has shown that positive and negative emotions are interrelated and that negative emotions are negatively correlated with motivation. It is, therefore, important to investigate how learners regulate their emotions. In this case study, one learner was closely observed over a period of 13 years. This learner claims that he has been feeling strong anxiety while learning English, but also that his negative emotion was the source of motivation to proactively study the language. The research used three types of data: (a) language learning historical records, (b) in-depth interviews, and (c) two questionnaires: the Foreign Language Classroom Anxiety Scale and the Strategy Inventory for Language Learning questionnaire. The results reveal the intense experience of the learner's emotions, as well as the significant shifts therein. It also unearths some of the sources of his emotional experiences and how he regulated these experiences. An important observation was the positive contribution that negative emotions had on some aspects of the participant's learning.